Adobe Premiere Pro : classroom in a book; the official training book from Adobe - Jago, Maxim, ....- (San Jose : Adobe Press, 2021)
The fastest, easiest, most comprehensive way to learn Adobe Premiere Pro Classroom in a Book (R), the best-selling series of hands-on software training workbooks, offers what no other book or training program does-an official training series from Adobe, developed with the support of Adobe product experts. Adobe Premiere Pro Classroom in a Book (2021 release) contains 17 lessons that cover the basics and beyond, providing countless tips and techniques to help you become more productive with the program. You can follow the book from start to finish or choose only those lessons that interest you. Purchase of this book includes valuable online features. Follow the instructions in the book's Getting Started section to unlock access to: Downloadable lesson files you need to work through the projects in the book DVD containing the lesson files are included with the print book Web Edition containing the complete text of the book that walk you through the lessons step by step What you need to use this book: Adobe Premiere Pro (2021 release) software, for either Windows or macOS. (Software not included.) Note: Classroom in a Book does not replace the documentation, support, updates, or any other benefits of being a registered owner of Adobe Premiere Pro software.
Keywords: Videobewerking